2010
DOI: 10.1210/en.2009-0788
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulin Signaling on Female Reproductive Function Independent of Adiposity and Hyperglycemia

Abstract: Physiological states of insulin resistance such as obesity and diabetes have been linked to abnormalities in female reproductive function. However, it is difficult to distinguish the direct effects of impaired insulin signaling from those of adiposity or hyperglycemia because these conditions often coexist in human syndromes and animal models of insulin resistance. In this study, we used lean, normoglycemic mouse lines with differing degrees of hyperinsulinemia and insulin receptor (Insr) expression to dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
0
24
0
3
Order By: Relevance
“…Similar studies in insulin-resistant and hyperinsulinemic mice demonstrated altered duration of estrous cycles as well as aberrant distribution and morphology of ovarian follicles [42, 49, 98]. The metabolic effects of insulin mainly involve tissue-specific actions which result in changes in gene expression, protein phosphorylation and function of the INSR and its downstream adaptor proteins, IRS1-4 [99].…”
Section: Discussionmentioning
confidence: 94%
“…Similar studies in insulin-resistant and hyperinsulinemic mice demonstrated altered duration of estrous cycles as well as aberrant distribution and morphology of ovarian follicles [42, 49, 98]. The metabolic effects of insulin mainly involve tissue-specific actions which result in changes in gene expression, protein phosphorylation and function of the INSR and its downstream adaptor proteins, IRS1-4 [99].…”
Section: Discussionmentioning
confidence: 94%
“…The selective reactivation of the IR under the transthyretin promoter, in which the re-expression of IR is restricted to the brain, hepatocytes, and pancreatic β cells, in mice otherwise null for IR improves fertility in both sexes (Okamoto et al, 2004). No deficits or very mild phenotypes were recorded in the length of the estrous cycle, ovarian histology, or reproductive fecundity (Nandi et al, 2010; Okamoto et al, 2004), highlighting the importance of IR expression in the brain and its control on fertility. Global deletion of IRS2 revealed a drastic reproductive phenotype.…”
Section: Leptinmentioning
confidence: 96%
“…Encouragingly, animal studies support these clinical findings. For example, lean and normoglycemic female mice exhibiting varying degrees of insulin resistance and hyperinsulinemia were shown to have subtle alterations in their HPG axis and also had polyovular follicles (Nandi et al 2010). Although insulin can act both peripherally and centrally to modulate HPG axis function, we know that insulin's central actions play a role in mediating many of its reproductive effects as mice exhibiting brain-specific deletion of insulin receptors (InsR) exhibit subfertility due to mild hypothalamic hypogonadism (Bruning et al 2000).…”
Section: Insulinmentioning
confidence: 99%